Characterization and Lipid Extraction of Amazon Cocoa Seeds [Theobroma grandiflorum] - Alviárez G., E.; Murillo A., W.; Murillo P., E.; Rojano, B. A.; Méndez A., J. J. (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The pulp from Theobroma grandiflorum, commonly known as Copoazú, is used to prepare jams, juices,yogurt, and nectars and sweets, while their seeds are exploited for the development of cupulate, a beverage which is the equivalent to chocolate. In Colombia, there are few reports about the properties of this fruit, especially about the fatty acids from its seeds, which could be of great interest in the food industry. Therefore, in this study were identified and analyzed the fatty acids content, which are present in the Copoazú seeds extracted oil, in its physiological maturity and analyzed its qualities indices. Also the fat antioxidant potential was measured by the ORAC essay. The above approach to understand the nourishing potential use of the food and/or nutraceutical, in one of the Amazon exotic fruits little known in Colombia. The identification of fatty acids showed that there is a high content of oleic (36.3%), stearic (29.27%) and palmitic acid (7.26%), plus, the qualities indices like the saponification (1.88,15 mg KOH/g sample), iodine (49.33 g de I/g oil) and acid (1.04 mg KOH/g sample) show that Copoazu oil could be used in food and cosmetic industries.